Numerical Evaluation of Seismic Response of Asymmetrical Reinforced Concrete Frame Buildings - J. Hamood, Mohammed; A. Ghalib, Layla; G. Abdalwahab, Ameer (International Journal of Engineering and Technology, 2018)
Asymmetrical multi-storey buildings are almost unavoidable in modern structures due to various types of useful and architectural requirements. Latest earthquakes showed that irregular distribution of mass, stiffness and strength cause serious damage in building structural systems. This paper investigates the numerical simulation of buildings with plan irregularity and presents a case study to demonstrate the numerical evaluation of the seismic response of a three real plan-asymmetric reinforced concrete building tested at full scale at the European Laboratory for Structural Assessment of the Joint Research Center, Ispra / Italy within the SPEAR project. The structural evaluation performed through a validated Finite Elements Package, modeled by the general purpose ABAQUS, which is able to run accurate analysis, in particular nonlinear static and dynamic analysis considering both geometric nonlinearity and material inelasticity. Adequacy of the numerical modeling is verified by comparing numerical and experimental results through evaluation of the seismic capacity and dynamic characteristics of the building. The provisions of the adopted seismic code for designing such buildings are also checked over and done with the nonlinear static and dynamic analysis by verifying the proficiency of an analytical model for simulating the nonlinear response of structures considered to conduct an investigation into experiments.